2022
DOI: 10.1155/2022/5165203
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Expression Significance of LPa, BNP, and McP‐1 in CHD Patients and Their Relationship with Echocardiographic Parameters

Abstract: In order to investigate the expression levels of Lipoprotein A (LPa), B-type Natriuretic Peptide (BNP) and Monocyte chemoattractor Protein-1 (McP-1) in serum of patients with coronary heart disease (CHD) are used to detect significance and to analyze the correlation between these indicators and parameters of echocardiography. The clinical data of 132 CHD patients in our hospital from January 2021 to October 2021 are retrospectively analyzed and included in the CHD group. Another 100 healthy people who came to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%